Experiências e saberes do enfermeiro em Cuiabá - Mato Grosso no século XIX - Santos, Elizabeth Jeanne Fernandes (2015)
Reflecting on the experience of the work of Brazilian nurse in the nineteenth century, it is important to understand the nurse's constitution processes as a professional and your education process. For this reflection, it was considered the search for meaning in the historicity of this social actor in Cuiabá. The formulation and awareness of the nurse in the nineteenth century as well as the constitution of the working class of nursing in Cuiabá - Mato Grosso, based on the art of caring, cultural, based on local customs, was the main focus of this research. In achieving the objectives, the experiences were explored, the knowledge that is articulated in regional and Brazilian level, to make up the field of nursing science of nurses in Cuiabá in the early nineteenth century. Were goals in the quest for analysis of experiences / caring practices found in the history of Cuiaba village, in the early nineteenth century: a) Outline the first practices of formation of health and governance institutions (policies) that emerged in this period, describing as were the functioning of institutions and existing regulations; b) To present and reflect on the credible daily care expressed in the various sources that offer nurse's features will be shown, and on the knowledge underpinning the practices / experiences; c) To reflect on the evolution of care practices found, always looking for the theme and the social representations of care performed by nurses and the possibilities of the transmission of caregiving experience. There was the need for change of posture of the analytical material found because the wealth of supply and local culture found required a different analytical and descriptive approach to the proposed object. So the timeline follows the theme and not the logic of time as in research carried out at certain times, so that the various sources that together this story could be included in this research. Thus, the methodological tactics form the narrative that seeks to meet the central questions of the research. The sources used were considered were: 1) images, which recorded the daily, in order to demonstrate the life; 2) official documents with evidence of the practices of care and morals to care, and 3) cultural registers (unofficial) such as chronic with representations of the Brazilian nurse. Relations between the internal and external social groups to institutions that performed the care, these established relationships that were played daily during procedures and care practices and teaching care. Spatial devices that formulated its maintenance are presented in images and texts found in the sources consulted, that exemplify the power devices used to establish the identity of the nurse caregiver. The European bourgeois thought post-Enlightenment, circulated in the Portuguese colonies and started in small social movements in the late seventeenth century thus changed the popular culture of caring, and the nurse who was revealed as a social actor's care, put in place the new habits required for care.